Implementasi Program Asuransi Usaha Tani Padi (AUTP) di Kecamatan Pauh Duo - Insan Kamillia, Wulan; Jumiati, Jumiati (PUBLICNESS: Journal of Public Administration Studies, 2025)
This research aims to analyze the implementation of the Rice Farmer Business Insurance Program (AUTP) in the Pauh Duo Sub-district, including identifying its supporting and inhibiting factors. Using a descriptive qualitative approach, data was collected through interviews and documentation. The implementation analysis uses the theory of Van Meter and Van Horn (1975). The result shows that the implementation of the AUTP Program in the Pauh Duo Sub-district has not been optimal. Of the six variables studied, three variables have been well implemented: resources, characteristics of implementing agents, and attitudes of implementers. Meanwhile, the other three variables still experience obstacles: policy standards and means, inter-organizational communication and activity strengthening, and political, economic, and social environmental conditions. This finding indicates the need for policy standardization improvement and coordination among stakeholders to optimize the implementation of the AUTP Program in the Pauh Duo Sub-district.